If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 4(1 + -1x) = 3x + 0(1 + -1x) -4x + (1 * 4 + -1x * 4) = 3x + 0(1 + -1x) -4x + (4 + -4x) = 3x + 0(1 + -1x) Reorder the terms: 4 + -4x + -4x = 3x + 0(1 + -1x) Combine like terms: -4x + -4x = -8x 4 + -8x = 3x + 0(1 + -1x) Anything times zero is zero. 4 + -8x = 3x + 0(1 + -1x) Reorder the terms: 4 + -8x = 0 + 3x Remove the zero: 4 + -8x = 3x Solving 4 + -8x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + -8x + -3x = 3x + -3x Combine like terms: -8x + -3x = -11x 4 + -11x = 3x + -3x Combine like terms: 3x + -3x = 0 4 + -11x = 0 Add '-4' to each side of the equation. 4 + -4 + -11x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -11x = 0 + -4 -11x = 0 + -4 Combine like terms: 0 + -4 = -4 -11x = -4 Divide each side by '-11'. x = 0.3636363636 Simplifying x = 0.3636363636
| 0.6w=0 | | 5p=30-10n | | 4x^2-x=17 | | 7j(8j-1)=0 | | 3x-5(1-x)=-2x+3(1-x) | | 1/5*x=210 | | 10.36+23.199x=56.758 | | (6x+7)(4x+3)=0 | | 3x+21=16x-10 | | 7c^4=-1512c | | -6÷(-3/7) | | -5x-66-6x+30=118 | | 5=-16t^2+26t | | -4x+3(1-x)=-5x+-1(1-x) | | 2x+-4(1-x)=-2x+-2(1-x) | | 96v^2-54=0 | | 2(3x+1)+5-3=x+22+2 | | ((3x/2x-1)-2)/((5/4x)-x/2x-1) | | -121=-y^2 | | (X+4)(x-1)=o | | 2/5a-1-3 | | (5/2)(3/10) | | 2x^2+12+18y^2= | | 0.3z-2=7 | | 25q^2=1 | | 6n=215 | | 3x-5(x+2)=-7 | | 2(2x+x)+10=2(x+10)+18-8 | | 9j(j-7)=0 | | y+2=3434(x+2) | | 8+5y=-22 | | 5/6(3/8) |